The Interplay of Gender and Ethnicity Towards Language Choice of Filipino Youth - Anniebelle Diaz (Yayasan Ilomata, 2022)
This study investigated on the most used languages of Filipino youth in the family domain of language used and investigated on the relationship of gender and ethnicity towards language use. A total of fifty-three individuals participated in the study who were aged between 15-24 and they were of different ethnicities. To gather the needed data for the study, a self-administered questionnaire was developed which was divided into two sections: (1) the first section of the instrument sought the necessary information as regards to the participants’ demographic profile which basically included the age, gender, and ethnicity; and, (2) the second section was composed of the twelve (12) different social events in the family domain to determine the language choice and its frequency of use in each of the social event. To analyze the data, SPSS software was used. describe the profile of the respondents and to determine the relationship of the variables. The study considered five under investigation languages, namely English, Tagalog, Chavacano, Bisaya, and Tausug. According to the results of the study, Tagalog was the most used language in the family domain of language use. Furthermore, in the family domain, both gender and ethnicity played no significant role in determining that language choice of Filipino individuals.